Guidelines for Reporting Quantitative Methods and Results in Primary Research. Issue 2 (June 2015) - Norris, John M.; Plonsky, Luke; Ross, Steven J.; Schoonen, Rob
<x xml:space="preserve">Abstract</x> Adequate reporting of quantitative research about language learning involves careful consideration of the logic, rationale, and actions underlying both study designs and the ways in which data are analyzed. These guidelines, commissioned and vetted by the board of directors of Language Learning, outline the basic expectations for reporting of quantitative primary research with a specific focus on Method and Results sections. The guidelines are based on issues raised in: Norris, J. M., Ross, S., & Schoonen, R. (Eds.). (2015). Improving and extending quantitative reasoning in second language research. Currents in Language Learning, volume 2. Oxford, UK.